The Contributions of Quranic Tahfidz to Mental Health - Trinova, Zulvia; wati, salmi (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
One of the miracles of the Quran is believed to influence the humanâs mental health, particularly to those who can memorize it.Â The Huffazh (Quranic Tahfidz) has been discussed in many verses, but only recently that scientific investigation gauged this issue, resulted in tremendous efforts to implant it among Muslim communities.Â The current study seeks to uncover the contribution of Quranic Tahfidz to mental health.Â Eight hundred and twenty- eight students studying Islamic Studies in the Faculty of Islamic Education and Teacher Training were interviewed, observed, and given questionnaires to find out their level of tahfidz and mental health.Â The findings revealed among other things that 62.5 percents of the respondents were the huffadz for 1 to 5 juz.Â The huffazh in 6 to 10 juz constituted 7.5 percents, and there were only 10 huffazhs who memorized up to 10 juz.